If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 5) = 32 Reorder the terms: 3(5 + y) = 32 (5 * 3 + y * 3) = 32 (15 + 3y) = 32 Solving 15 + 3y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3y = 32 + -15 Combine like terms: 15 + -15 = 0 0 + 3y = 32 + -15 3y = 32 + -15 Combine like terms: 32 + -15 = 17 3y = 17 Divide each side by '3'. y = 5.666666667 Simplifying y = 5.666666667
| 5m+5.25=42.75 | | -1-2g=1 | | -20+12r+6q-2r-3q-26= | | 0/27=x | | 2(a+2b)-(a-b)= | | 9+4r=1 | | 19=19h-19 | | 5=v+1 | | 1/6d+2/3=1/4(d-2) | | -4+15=11 | | sinA=0.5 | | 7x-8-5x=0 | | 118=-5(-4-4p)-6p | | -4+15=x | | 7c-2c=42 | | x-6-17=-13 | | -7z+4+16-8z= | | X^3-6x+10x-8=0 | | 15=12k-9 | | a+(a+10)=16 | | -4c+9(3c+5)= | | 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= | | 2x-39=21 | | 8t+1=-7 |